Investigating Yūsuf al-Qaraḍāwī’s Approach Towards Inter-Religious Encounters in the Light of His Teachings and Writings - Moahmed Rasak, Mohamed Arkam; Fatmir Shehu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research seeks to investigate the approach of Yusuf al-Qaradawi toward inter-religious encounters in the light of his teachings and writings. As a prominent Islamic scholar and intellectual, Qaradawi’s teachings and writings have had a significant impact on the relationship between the Muslim community and others. The goal of this research is to provide an analysis of Qaradawi’s writings and teachings to extract his approach toward inter-religious encounters and relations, drawing on a range of primary and secondary sources. Through a critical examination of his views on this subject, the approach of Qaradawi toward inter-religious understanding and cooperation is emphasized. The descriptive, analytical, and critical methods are used in the entire work. A brief description of Yusuf al-Qaradawi’s life, intellectual development, and works on inter-religious encounters and understanding is provided. Analysis of how he approached inter-religious encounters and relations, and how his views and thoughts on this subject have been received by both Muslim and non-Muslim communities. The study expects to provide new insights into Yusuf al-Qaradawi’s approach to inter-religious engagements, which are relevant to the contemporary context of inter-religious relationships between Muslims and adherents of other religions.